Meta-analysis Study: The Effect of the Independent Curriculum Integrated Project Based Learning Model on Student Learning Outcomes in Natural Science Materials - Yayat Suharyat; Ichsan Ichsan; Agus Supriyadi; Tomi Apra Santosa; Aulia Sofianora (Badan Penerbit STIEPARI Press, 2023)
In the era of Revolution 5.0, world society experienced rapid development, especially in the world of education. Education today has enabled technology to assist the learning process. The learning process in the Industrial Revolution era (5.0) required students to master learning technology. In addition, teachers have an important role as educators in facilitating students. However, teachers have not been able to carry out learning in accordance with the independent curriculum. The independent curriculum remains the primary impediment for teachers in encouraging student learning outcomes in the classroom. In the independent curriculum, students must be creative and innovative in their learning. Independent curriculum-guided teachers must be able to apply the project-based learning model. The purpose of this study was to analyze the effect of the project-based, integrated learning model of the independent learning curriculum on student learning outcomes. This type of research is a type of meta-analysis research. The data source comes from an analysis of 15 national and international journals indexed by SINTA, Copernicus International, and DOAJ. The search for data sources comes from the Google Scholar database and the Eric Journal. The data collection technique is a direct observation technique that involves tracing articles that have a relationship with the research variables. The search keywords for data sources are the PjBL learning model, independent curriculum, and learning outcomes. The data analysis technique is a quantitative statistical technique, with the help of the OpenMEE application. Data analysis was performed by calculating the effect size, standard deviation, average, and N-gain values. The results of the study concluded that the PjBL learning model integrated with the independent curriculum had a significant influence on student learning outcomes. This can be seen from the effect size value of 2.67, SD of 6.03, average student score of 89.56, and N-Gain of 4.20. The use of the PjBL model in the independent curriculum benefits both teachers and students as they prepare for the twenty-first century. In order to implement the Pjbl model in schools, teachers must be professionals